2000
DOI: 10.1016/s0022-3913(00)70067-9
|View full text |Cite
|
Sign up to set email alerts
|

Hardness of celluloid strip-finished or polished composite surfaces with time

Abstract: THE JOURNAL OF PROSTHETIC DENTISTRY VOLUME 83 NUMBER 6The smoothest composite surface that is important in esthetic restorations can be obtained with a celluloid strip. 1 However, a discoloration study revealed that composite surfaces polymerized under matrix discolored more than surfaces polished after 48 hours of light curing. 2 Higher tendency of discoloration on the celluloid strip-covered composite surface, even though it has a smoother surface, may be related to lower physical property on the surface.A p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 16 publications
3
16
0
4
Order By: Relevance
“…This indicates that additional polymerization occurred during the five days in which the specimens were stored, in agreement with the results from several previous studies. 4,[13][14][15] Non-reacted free radicals remain in composites even after light activation and react with free monomers to produce a continued polymerization chain reaction. This additional polymerization by free radicals occurs considerably during the first hour and has been reported to persist over the course of one month.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This indicates that additional polymerization occurred during the five days in which the specimens were stored, in agreement with the results from several previous studies. 4,[13][14][15] Non-reacted free radicals remain in composites even after light activation and react with free monomers to produce a continued polymerization chain reaction. This additional polymerization by free radicals occurs considerably during the first hour and has been reported to persist over the course of one month.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the type of composite used, the thickness of the OIL is between 10 and 200 μ m. [1][2][3] The OIL adversely affects the prognosis of composite restorations since it reduces surface hardness, wear resistance, and marginal adaptation of composite restorations. [3][4][5] The OIL cannot be completely removed by occlusal adjustment, finishing, or polishing procedures after curing, and the partial remnants of the OIL reduce the quality of the final restoration. Therefore, in order to minimize the OIL as much as possible, its formation can be reduced by curing the composite after inhibiting oxygen contact either through the use of a Mylar strip or application of glycerin to the composite surface.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that the microhardness of a celluloidstrip finished composite surface was lower than the composite surface itself. 18 Finishing the composite surface with a celluloid-strip can produce the smoothest composite surface. However, the celluloid-strip finished composite surface discolors more than a polished one, probably due to its high resin concentration on the surface.…”
Section: Discussionmentioning
confidence: 99%